PERGESERAN TATA CARA PERNIKAHAN ADAT JAWA YOGYAKARTA DI KECAMATAN TAPUNG KABUPATENKAMPAR - Fifit Fitriani; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by a shift in Javanese traditional marriage in Yogyakarta in the District of Tapung in the Kampar District in the manner in which the marriage is conducted. The formulation of the problem of this research is